The real and financial effects of internal liquidity: Evidence from the Tax Cuts and Jobs Act - Albertus, James F.; Glover, Brent; Levine, Oliver (Journal of Financial Economics, 2025)
The Tax Cuts and Jobs Act unlocked as much as $1.7 trillion of U.S. multinationals’ foreign cash. We examine the real and financial response to this liquidity shock and find that firms did not increase capital expenditures, employment, R&D, or M&A, regardless of financial constraints. On the financial side, firms paid out only about one-third of the new liquidity to shareholders and retained half as cash. This high retention was not associated with poor governance. The high propensity to retain the liquidity shock as cash, even among well-governed firms with limited financial constraints, is difficult to reconcile with existing theory.